(untitled) (Atti del Sodalizio Glottologico Milanese, 2019)
The present study aims at dealing with several questions related to the conceptual and terminological frame of metalanguage, a technical term that plays a crucial role in the linguistic reflection, since Alfred Tarsky’s codification through the amplified value assigned to the term from Roman Jakobson. First of all the Author presents the original Eugenio Coseriu’s contribute to the general characterization of the construct; then a indepth study of the metalinguistically relevant notions in the Coseriu’s work is given. In particular the Romanian linguist builds a model founded on terminological three-way distributions: for example designazione, significazione, senso; ’sistema, norma y habla’ etc. A peculiarity and at the same time an evidence of his influence is the Italian use of sp. cambio with the meaning of change. In conclusion the terminological and conceptual tools that Coseriu forged in treating language have become part and parcel of modern linguistics. KEYWORDS: Coseriu, metalanguage, history of linguistics, theoretical linguistics, metalinguistic concepts